Reliability Assessment of Electrohydraulic Actuation Control System Subject to Multisources Degradation Processes - Xu, Dan; Feng, Zhixin; Sui, Shaobo; Lin, Yan-Hui (IEEE/ASME transactions on mechatronics, 2019)
The electrohydraulic actuation (EHA) control system is commonly utilized in aeronautic industry, such as in undercarriage control system, and plays an important part in preserving the security and stability. This article proposed a piecewise deterministic Markov process (PDMP) based modeling framework for the reliability assessment of EHA closed-loop control system subject to multisources degradation processes. The multisources degradation integrally consists of continuous and discrete degradation processes of different electrohydraulic components, caused by wear and input variation. The dependence among the multisources degradation processes is explicitly modeled based on the PDMP modeling framework. The failure criteria of EHA closed-loop control system are proposed, which involve the settling time, overshooting value, and steady-state error of output. Furthermore, the Monte Carlo simulation is employed to compute the system reliability. An EHA closed-loop control system used in the aeronautic undercarriage system is presented as an illustrative case to demonstrate the effectiveness of the proposed framework.